Extraction of bioactive compounds from cacao pod husks (CPH) - Dewi, Shinta Rosalia (2023)
In Indonesia, approximately 505-kilo tonnes of fresh cacao pod husk (CPH) are discarded annually as a primary waste by-product during cacao production. Although they can be directly applied as fertiliser or animal feed, most of them are left on farms, causing environmental issues that could reduce cacao productivity. In the meantime, CPH contains bioactive compounds, including phenolics and anthocyanins, which have promising antioxidant activity. Therefore, recovering bioactive compounds from CPH by solvent extraction is a promising sustainable way to both avoid waste and valorise it as a new renewable resource. The aim of this research was to study how the processing parameters can maximise the extraction yields and consider process efficiency when designing a flowsheet of CPH valorisation. A systematic extraction research was studied to understand the influence of material pretreatment (drying and size reduction), solvent type, and different heating methods (conventional and microwave) on extraction yields. How other system variables (extraction time and temperature, solvent concentration and solvent-to-feed ratio) interact within conventional and microwave heating was also investigated to maximise yields. The work presented in this thesis can first demonstrate that CPH contained up to 107.3 mg GAE/g dw of phenolics including 0.37 mg Cy3GE/g dw of anthocyanin with good antioxidant activity (up to 4.6 mg TE/g dw or ~ 94% radical scavenging). Phenolic and anthocyanin compounds were concentrated in CPH epicarp layer, while antioxidant was found maximum in CPH endocarp layer. Solvent type and material pretreatment (size reduction and drying) were very influential in maximising the extraction yields. Size reduction enhanced the phenolic and anthocyanin yields significantly but had no significant effect on the antioxidant activity of extract. Phenolic compounds, including anthocyanins, were highly extracted in aqueous ethanol (50% iii (v/v) ethanol/water) due to their similar solubility based on Hansen Solubility Parameter (HSP) value. However, the highest antioxidant activity was found in the ethanolic extract (100% (v/v) ethanol) due to protic solvent effect. In terms of the heating method, microwave has been regarded as a promising extraction method due to its volumetric and selective heating, which allows for rapid heating and increased yield. A comparison of MAE and CSE at a similar heating rate (by neglecting microwave volumetric heating) demonstrated no differences in optimum extraction time, solvent concentration and solvent-to-feed (S/F) ratio for both methods but a difference in extraction yields. The best time to extract bioactive compounds was 5 min because a longer extraction time resulted in lower bioactive yields. In contrast, extraction temperature had varying effects: increasing temperature can increase the phenolic yields while decreasing anthocyanin and antioxidant yields. MAE at 60 °C had 5% higher phenolic yield than CSE, which was attributed to a selective heating effect. Meanwhile, extracting anthocyanin and antioxidant compounds was favoured at low temperature (50 °C) to prevent degradation despite no selective heating effect. Additionally, the CPH solid residue from the extraction process still has a potential to be valorised into other valuable products, such as bio-oil, non-condensed gases and activated carbon, due to its proximate and lignocellulosic contents. This study, therefore, can be used as input data in the preliminary engineering design of CPH valorisation flowsheet to select an efficient process and assess its viability. The usage of CPH as new resource material for the production of high-value products has the potential to increase its economic value while reducing waste.